Inequalities in the UK : new discourses, evolutions and actions - Fée, David (Lecturer); Kober, Anémone, 1962- (Bingley, U.K. : Emerald Publishing Limited, 2017)
This book addresses the question of the extent of and responses to inequalities in the UK in 2017 in the wake of the 2008 Great Recession. Inequality is the issue that won't go away, a real world issue affecting all facets of society with political and economic developments such as austerity measures, Brexit and changes in political leadership impacting the inequality landscape. Six of the chapter examine the extent of economic inequalities and poverty using quantitative and qualitative methods that help map regional differences, compare the UK with the rest of the EU and go beyond the traditional measures and concepts. Seven chapters explore how inequalities have evolved since 2008 and have been tackled by policy makers in five policy areas (health, housing, education, gender and immigration) taking into account the new legislative framework and in one party (labour). Finally, six others address the issue of the governance of inequality by looking at how inequality features in the political agenda of the devolved assemblies in Northern Ireland, Scotland, Wales as well as at a local level in Ipswich and London. Based on recent surveys and current academic thinking, this book provides an up-to-date account of the extent and distribution of inequalities in the UK, of the evolving ways in which inequalities are measured and addressed as well as the changing perception of inequalities by the general public and policy-makers.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Equality -- Great Britain; Great Britain -- Social conditions -- 21st century; Great Britain -- Politics and government -- 21st century